Smart gold nanoparticle-stabilized ultrasound microbubbles as cancer theranostics. Issue 20 (10th May 2018) - Yoon, Young Il; Pang, Xin; Jung, Sungwook; Zhang, Guofeng; Kong, Minsuk; Liu, Gang; Chen, Xiaoyuan
Abstract : Smart gold nanoparticle-stabilized ultrasound microbubbles (SAuMBs) having diagnostic (US and PAT) and therapeutic (PTT) effects were applied as cancer theranostics. Abstract : Smart gold nanoparticle-stabilized microbubbles (SAuMBs) composed of a gas-filled core and shell including smart gold nanoparticles (SAuNPs) which can be aggregated in tumors were applied as ultrasound-mediated cancer theranostics. The gas core in the microstructure enabled the detection of tumors using ultrasound and facilitated the delivery of SAuNPs by sonoporation. The SAuNPs spontaneously aggregated in tumors, which allowed photoacoustic (PA) monitoring and photothermal treatment (PTT) of tumors.